Valuation of risk and complexity attributes causing delays in Australian Transport infrastructure projects for optimal contingency Estimation - Jayakumari, Praveen Mohandas (Curtin University, 2022)
The transportation projects have historically experienced significant delays and cost overruns from the time decision to build has been taken by the owner. This thesis addresses the problem of why this delay occurs by looking at the drivers from a risk management perspective. It identifies and analyses the owner risk attributes that contribute to significant delays related to transportation projects from an Australian context. After a literature review of current risks causing delays in transportation projects from across the globe, risk and complexity related to transport projects in Australia are identified from an Australian context using a questionnaire survey completed by participants with relevant experience in the transport industry. The risks are ranked using the Relative Importance Index (RII) based on likelihood and impact score. The results obtained include many attributes which are condensed to factors based on correlations using factor analysis. This gives us a big picture of the main risk and complexity factors affecting delays on transportation projects. Once done, a predictive model is obtained between the overall delay as the dependent variable and risk attributes as the independent variable. This is obtained using the statistical technique of Ordinal Multivariate regression. Lastly, a working framework that allows the methodology used in the thesis to be applied to all projects to understand the risk and complexity factors. This result can be useful for owners in obtaining a realistic design to build estimate in transport infrastructure projects by allocation of suitable contingency on risk and complexity drivers causing delays in transport infrastructure projects